Facets of Indology : Mahamahopadhyaya Pandit Damodhar Mahapatra Shastri commemoration volume - Damodhar Mahapatra Shastri; Subash Chandra Dash(ed.) (Pratibha Prakashan, 2005)
Festschrift in honor of Damodhar Mahapatra Shastri, 1890-1975, Sanskritist; comprises research articles on Vedic literature, religion, and Sanskrit grammar.